2020
DOI: 10.1039/d0ta00284d
|View full text |Cite
|
Sign up to set email alerts
|

A self-supported 3D aerogel network lithium–sulfur battery cathode: sulfur spheres wrapped with phosphorus doped graphene and bridged with carbon nanofibers

Abstract: An integrated PGCNF/S aerogel with a “network” structure has effectively restricted the shuttling of polysulfides and exhibited promising lithium ion storage capability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(41 citation statements)
references
References 91 publications
3
38
0
Order By: Relevance
“…Figure 6 c shows the electronic localization function of the C–N model. It is found that nitrogen doping decorates the electronic structure of the carbon layer, which can be observed as the net gain of electronic charge between the nitrogen atom and carbon layer [ 58 ]. This phenomenon illustrates that a charge can be transferred from the nitrogen doping atom to its nearest neighboring carbon atom [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 6 c shows the electronic localization function of the C–N model. It is found that nitrogen doping decorates the electronic structure of the carbon layer, which can be observed as the net gain of electronic charge between the nitrogen atom and carbon layer [ 58 ]. This phenomenon illustrates that a charge can be transferred from the nitrogen doping atom to its nearest neighboring carbon atom [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is found that nitrogen doping decorates the electronic structure of the carbon layer, which can be observed as the net gain of electronic charge between the nitrogen atom and carbon layer [ 58 ]. This phenomenon illustrates that a charge can be transferred from the nitrogen doping atom to its nearest neighboring carbon atom [ 58 ]. Furthermore, we also find that the Fermi level of the C–N model is shifted right up to the conduction band with the additional nitrogen doping according to the calculation results of the electronic density of states.…”
Section: Resultsmentioning
confidence: 99%
“…107 CVD, chemical vapor deposition; GO, graphene oxide; rGO, reduced GO design of aerogels. Tan et al 111 prepared CNF by electrospinning and obtained a fishing net structure wrapping sulfur nanospheres via in-situ growth, inside P-doped graphene aerogels. The CNF fishing net serves as a bridging network between graphene sheets to inhibit the aggregation and enhance the ion and electron transport capacity of the electrode.…”
Section: Two-dimensional Nanocarbonmentioning
confidence: 99%
“…As a result, the initial and final capacity after 200 cycles are 1480 and 957 mAh g −1 , respectively, at a high current density of 1 C. The latest graphene‐based self‐supporting electrodes started working with the structure design of aerogels. Tan et al 111 prepared CNF by electrospinning and obtained a fishing net structure wrapping sulfur nanospheres via in‐situ growth, inside P‐doped graphene aerogels. The CNF fishing net serves as a bridging network between graphene sheets to inhibit the aggregation and enhance the ion and electron transport capacity of the electrode.…”
Section: Carbon Substrates For Lsbs Flexible Cathodesmentioning
confidence: 99%
“…However, most of these carbon interlayers cannot effectively adsorb polysulfides and inhibit the ''shuttle effect", due to the lack of active sites that can adsorb the polysulfides through chemical interactions [29]. Therefore, doping carbon materials with various heteroatoms, such as nitrogen (N) [30][31][32], oxygen (O) [33], phosphorus (P) [34,35], sulfur (S) [36], boron (B) [37,38], and fluorine (F) [39] is a reasonable method to introduce polar sites for adsorption of the dissoluble polysulfides [40]. Doping carbon materials with N can efficiently improve the conductivity of materials, and the strong adsorption interaction between O and polysulfides can inhibit the diffusion of polysulfides, which further leads to an improved utilization of the active materials [40].…”
Section: Introductionmentioning
confidence: 99%